Standardization of Semanggi (Marsilea crenata C. Presl.) Leaves from Benowo District, Surabaya for Standardized Herbal Raw Material - Burhan Ma'arif; Almay Abidzar Elpasha; Arief Suryadinata; Tanaya Jati Dharma Dewi; Novia Maulina; Mangestuti Agil (Universitas Pakuan, 2023)
Semanggi (Marsilea crenata C. Presl.) is a unique plant that grows in East Java, Indonesia. Its leaves are widely used as ingredients for traditional food. Semanggi leaves contain phytoestrogen compounds that can be used for their antineuroinflammatory, antiosteoporosis, and antioxidant properties. This effect is believed to be caused by kaempferol as an active marker. This study aims to determine the specific and non-specific parameters of semanggi leaves from Benowo District of Surabaya. The standardization results for specific parameters revealed the macroscopic characteristics of the leaves in radius ± 2 cm, pale green to yellowish-green color, smooth surface, obdeltoid shape, and four leaves. The microscopic features are stomata on the epidermis, crystal sand calcium oxalate, bone leaves with vascular bundle, and no space between the epidermis. The organoleptic characteristics are yellowish-green color, tasteless, astringent smell. The physicochemical of water-soluble content result was 7.4566 ± 0.1173% and soluble ethanol was 7.7466 ± 0.4083%. The phytochemical positive test results for the identification of alkaloids, flavonoids, and terpenoids. Based on UHPLC-HRMS analysis, semanggi leaves contain 0,41% kaempferol with a retention time of 6.88 ± 0.2 minute. The results for non-specific parameters indicated that the content of total ash, acid-insoluble ash, moisture, and drying shrinkage content was 0.8136 ± 0.0171%; 7.9700 ± 0.1044%; 6.2547 ± 0.2864%; and 9.0936 ± 0.1305% respectively. The results indicate that the semanggi leaves sample have been assessed and found to meet the established standards.